Pengaruh Penambahan Konsentrasi Logam Seng (Zn) Pada Proses Electrowinning Logam Kobal (Co) - Saputro, Adii (Chem Info Journal, 2013)
The Cobalt (Co) is a metal that is found in the same mine. Taking cobalt metal proved very difficult in electrolysis process. Electrowinning Co process needs to be studied in order to obtain as pure metal content in the process of separating the two. This research was conducted with the fixed potential in 2,3 volt electrolysis method within HCl as electrolyte. Electrodes used are carbon graphite. This experiment used variations addition of Zn2+ 105, 110, 115, and 120 mgL-1 in 100 mL of Co2+ 1100 mgL-1. The results showed the effect of the addition of Zn2+ to Co2+ changes in electrowinning overvoltage (Î·E) from 0.106 volts to 0.666; 0.646; 0.706, and 0.546 volts at each variation. Value tends to increase the current efficiency (Î·i) of each variation of 8.39%, 12.51%, 21.40% and 121%. The results of the reduction of Co2+ increased respectively 1.8%, 2.5%, 4.36% and 24.72%, while the reduction of Zn2+ declining 62.82%, 56.36%, 19.13 %, 10% in each variation. The color of the solution changed from pink to orange-yellow.